SLANG DALAM LIRIK-LIRIK LAGU CHRIS BROWN - WINDA, DEVIYANTI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACT This skripsi is entitled â€œSLANG DALAM LAGU-LAGU CHRIS BROWNâ€. The aims of this research are to analyze, identify and classify the words that use slang words of Chris Brownâ€™s songs. The purpose of this research is to analyze the types of slang by using song lyrics of Chris Brownâ€™s songs.Â The research uses descriptive method. The theory of Elissa Matiello (2008) and Leech theory (1998) are used in this research. The data were collected by listening to 10 songs by Chris Brown and reading the lyrics of the songs. The result of this research shows that there are four forms of slang in Chris Brownâ€™s songs namely, blending, clipping, copy reduplicatives, variation. The results of this research also shows that there are four meanings of slang in Chris Brownâ€™s songs namely, conceptual meaning with 63 data, connotative meaning with 2 data, thematic meaning with 2 data, social meaning with 2Â data. ______________________________________________ Key words: Slang,Meaning, Chris Brownâ€™s songs, Sociolinguistics.